Classification of Healthy and Diseased Arecanuts using SVM Classifier - Chandrashekhara, H; Suresha, M (International Journal of Computer Sciences and Engineering, 2019)
Arecanut is the seed of the areca palm (Areca catechu), Arecanut palm is one of the important commercial crops in India. Majority of arecanut are produced and consumed by Indian populations when compared to other countries. This paper proposes, to Classify Healthy and Diseased Arecanut images. In this paper Healthy and diseased arecanut are have been done. Structured matrix decomposition model (SMD) is used to segment the images and LBP features are extracted using SVM classifier. Experimental results demonstrate proposed method perform well and obtained accuracy of 98%.